Anda di halaman 1dari 2

# Problem No. 1102. (Proposed in The College Mathematics Journal, Vol. 48, No.

3,
May 2017.) Prove, for all nonnegative integers n, that

n   bn/3c   
X 2k X
n3k nk 2k
= 3 .
k=0
k k=0
2k k

## Solution. Recall that the generating function

P of a sequence (an )n0 is the function
n
defined by the infinite series F (x) = n=0 an x . We will use the fact that two
sequences with the same generating function are in fact the same sequence.

So, we start by finding the generating function of the sequence formed by the values
of the left hand side for n 0 (rearranging summation terms as long as the series
converges absolutely):

X n  
X 2k n
FL (x) = x
n=0 k=0
k
X  
X 2k m+k
= x where (m = n k)
m=0 k=0
k
 
X
m
X 2k k
= x x
m=0 k=0
k
1 1
= for |x| < ,
(1 x) 1 4x 4

where we have used that 1 is the generating function of the central binomial
14x
coefficients.
Next, we compute the generating function for the values of the right hand side:
bn/3c   
n3k n k 2k n
X X
FR (x) = 3 x
n=0 k=0
2k k
   
X 2k 3k X n k
= 3 (3x)n
k=0
k n=3k
2k
   
X 2k 3k X m + 2k
= 3 (3x)m+3k (m = n 3k)
k=0
k m=0
2k
   
X 2k 3k X m + 2k
= x (3x)m
k=0
k m=0
m
 
X 2k 3k
= x (1 3x)2k1
k=0
k
 k
x3

1
X 2k
= (1 3x)
k=0
k (1 3x)2
1
= (1 3x)1 q
4x3
1 (13x)2

1
= .
(1 x) 1 4x

Since FL (x) = FR (x) we have that both sides of the given expression are defined by
sequences with the same generating function, and consequently those sequences must
be equal.
